2008
DOI: 10.1152/ajpcell.00148.2007
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia effects on cell volume and ion uptake of cerebral microvascular endothelial cells

Abstract: Increased transport of Na across an intact blood-brain barrier (BBB) contributes to cerebral edema formation in ischemic stroke. Our previous studies have shown that ischemic factors stimulate activity of a luminal BBB Na-K-Cl cotransporter, and we have hypothesized that during ischemia, the cotransporter together with the abluminal Na/K pump mediates increased transport of Na from blood into the brain. However, it is possible that elevated Na-K-Cl cotransporter activity could also cause cell swelling if it ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
38
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 45 publications
6
38
0
1
Order By: Relevance
“…Furthermore, we have shown that CMEC exposed to moderate-to-severe hypoxia do not swell or exhibit significant increases in Na content until 3 or more hours after the onset of hypoxia, a finding consistent with increased NKCC and NHE activities contributing to BBB secretion of Na from blood into brain during the early hours of stroke rather than simple swelling of the endothelial cells (12,21). However, CMEC swelling observed after 5-h exposure to hypoxia is abolished in the presence of bumetanide and HOE-642, suggesting that both NKCC and NHE participate in the gradual swelling of the cells that occurs with hypoxia (12). There is evidence that the rapid astrocyte swelling that occurs during cerebral ischemia also involves NKCC and NHE activities.…”
supporting
confidence: 72%
“…Furthermore, we have shown that CMEC exposed to moderate-to-severe hypoxia do not swell or exhibit significant increases in Na content until 3 or more hours after the onset of hypoxia, a finding consistent with increased NKCC and NHE activities contributing to BBB secretion of Na from blood into brain during the early hours of stroke rather than simple swelling of the endothelial cells (12,21). However, CMEC swelling observed after 5-h exposure to hypoxia is abolished in the presence of bumetanide and HOE-642, suggesting that both NKCC and NHE participate in the gradual swelling of the cells that occurs with hypoxia (12). There is evidence that the rapid astrocyte swelling that occurs during cerebral ischemia also involves NKCC and NHE activities.…”
supporting
confidence: 72%
“…Rats with DKA manifest a reduction of apparent diffusion coefficient (ADC) values for brain water, indicating cytotoxic edema, and administration of the Na-K-Cl cotransport inhibitor bumetanide, which has been shown to reduce both astrocyte and brain microvascular endothelial cell swelling under hypoxic and ischemic conditions (13)(14)(15)(16)(17), returns ADC values to normal (18). These findings are similar to those in experimental models of stroke (18 -20).…”
supporting
confidence: 70%
“…Under ischemic conditions, the luminally located NKCC1 in BBB was functionally upregulated and played an important role in ionic edema and swelling of the brain parenchyma (Kahle et al, 2009;Wallace et al, 2011). In addition, there were evidences showing that hypoxia alone could stimulate the endothelial NKCC1 activity in BBB (Kawai et al, 1996;Brillault et al, 2008). Therefore, the neuroprotective effects mediated by BBB-located NKCC1 may contribute to the suppressing seizure activity of bumetanide.…”
Section: Effects Of Hypoxia-induced Neonatal Seizures On Eeg Seizuresmentioning
confidence: 99%